ARABIC AS A GLOBAL LANGUAGE - Rahimjanov Masrur Nugmanovich (Academia Science Repository, 2023)
Arabic has played a significant role in the linguistic development of the peoples of the Middle and Near East and is currently one of the most widely spoken languages in the world. It is spoken by about three hundred million people, or about 3% of the total population of the planet, which puts it on par with other global languag es (English, Hindi, and Spanish)